On affection and uniforms: military management and emotionality in shelters for Venezuelans in Roraima, Brazil - Vasconcelos, Iana dos Santos (2022)
This article aims to discuss the impact of emotions on the execution of government policies. In the specific case, the place of affective reactions in the behavior of Brazilian military personnel whose mission is to shelter Venezuelan migrants and asylum seekers in Boa Vista, Roraima. Based on ethnographic data collected through interviews and field observation, we contrast the "official reception", supposedly impersonal, and the "emotional reception" which is affected by the suffering of the Other. The military's double bind with maintaining order and with social assistance reveals the ambivalence of the so-called Operation Acolhida as a policy of securitization and humanitarian mission. The article revolves around the implications of an "emotional discontinuity" for the continuity of state action, presenting the military as a cyborg person, transitory of emotion and discipline, at the same time skin and uniform.